The SNOJIV: an innovative and inclusive educational system based on intelligent organization (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2026)
SNOJIV was founded in 1975 as a systemic structure that generates social relationships based on the motto “play and fight.”, with the initial purpose of reforming academic music education. This scientific article raised the following questions: What defines SNOJIV as an inclusive and innovative education system? What are the elements that characterize the System as an intelligent organization? To answer these questions, we worked with a triangulation of qualitative structural methods, which were: a) phenomenology b) focus groups discussion y c) the hermeneutic-dialectic method. Conclusion: by creating SNOJIV the reformation of musical education has been consolidated as an inclusive, flexible, intelligent, and open to change based on intelligent communication.
Keywords: SNOJIV; reformation of musical education; play and fight; inclusive education system; intelligent organization